Effect of Stress Ball on Stress and Anxiety in Hemodialysis Patients - Nurdina, Gina; Anggraini, Dian; Herdiman; Hilda Novyanda (STIKep PPNI Jawa Barat, 2022)
Introduction: Chronic kidney disease patients undergoing hemodialysis therapy experience various physical and mental problems that contribute to psychological disorders such as stress and anxiety. It can affect the mental and physical components of poor quality of life. A stress ball is one of the therapies that is considered the cheapest and easiest to use for dealing with stress and anxiety. Purpose: To determine the effect of Stress Ball on Stress and Anxiety in hemodialysis patients. Methods: The research design is a quasi-experimental one-group pre and post-test. The research sample was 34 hemodialysis patients members of Komunitas Pasien Cuci Darah Indonesia Jawa Barat (KCPDI West Java) with consecutive sampling techniques. Bivariate analysis using paired t-test. Respondents were asked to squeeze a stress ball for approximately 20-30 minutes in eight successive dialysis sessions. The instruments used are the Distress thermometer (DT) and Beck Anxiety Inventory (BAI). Results: Stress ball intervention affects stress and anxiety levels in HD patients with each P-value of 0.000. The average difference between pre-test and post-test stress levels is 1.55 with the at-count value of 6.95 > t-table 2.03. At the same time, the difference between the average pre-test and post-test anxiety levels is 5.74 with an at-count value of 6.25> t-table 2.03. Conclusion: Stress ball has been proven to reduce stress and anxiety levels in hemodialysis patients. Suggestion: Stress balls can be non-pharmacological therapy to reduce stress and anxiety problems for hemodialysis patients.